THE IFLUENCE OF TPS LEARNING MODEL (THINK PAIR AND SHARE) TO STUDENT’S LEARNING OUTCOMESS ON THE USAGE OF TOOLS-MEASURING INSTRUMENT (MEASURING TOOLS) FOR CLASS X TKR SMK KARSA MULYA PALANGKA RAYA AT ACADEMIC YEAR 2015/2016 - Bintar Tua Ompusunggu; Sanggam R.I Manalu (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
The difficulties encountered by the students to understand the material using Tools-Measuring Instrument (Measuring Tools) learning model Conventional can be seen on the learning outcomes of students who reach a level of mastery learning by 52% and 48% of student learning outcomes are not reached KKM that existed at the school is 70. This study aims to determine the effect of the learning model TPS student learning outcomes on the material using Tools - Measuring Tools (Measuring Tools) in class X SMK Karsa MulyaPalangkaraya Academic Year 2015/2016. This study uses pretest and posttest control group design. The study population was a class X Lightweight Vehicle Engineering, Mechanical Motorcycle A. This study sampled by simple random sampling classes and class X results obtained as a class Light Vehicle Engineering Experiment with the number of 40 students, and the class X Motorcycle Engineering A as a control class with the number of 38 students. Data is collected using the test, which consisted of pretest and posttest. The collected data were analyzed statistically using the average - average pretest, posttest and the difference in the two - average. Based on the results of data analysis of pretest value, there was an average class experiment (53.36) and the control class (51.76). It can be categorized not good, because it has not reached the KKM. Posttest data value - average class experiment (81.30) and the control class (71.34) were meaning that the class has reached KKM with a considerable level difference between before and after the treatment given deberikan Treatment (treatment). From the results of the analysis showed that the results of class X student of SMK Karsa Mulya Palangkaraya Normal distribution. Based on statistical analysis we concluded that "There Influence Learning Model TPS (Think Pair and Share) on the material using Tools Measure (Measuring Tools) in class X SMK TKR Karsa Mulya Palangkaraya". Based on these results it shows that the effect of student learning outcomes that occur in class experiments with learning model TPS is better than than the control class with conventional learning models on the material using Tools Measure.